2022
DOI: 10.1186/s12864-022-08666-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of R2R3-MYB gene family and association with anthocyanin biosynthesis in Brassica species

Abstract: Brassica species include important oil crops and vegetables in the world. The R2R3-MYB gene participates in a variety of plant functions, including the activation or inhibition of anthocyanin biosynthesis. Although previous studies have reported its phylogenetic relationships, gene structures, and expression patterns in Arabidopsis, the number and sequence variation of this gene family in Brassica crops and its involvement in the natural quantitative variation in anthocyanin biosynthesis regulation are still l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
(78 reference statements)
3
6
1
Order By: Relevance
“…4, Supplementary Table S2). This was different from the results we discovered that only PAP1/2 homologous copies were differentially expressed in green and purple leaves of five Brassica crops [5], indicating the different transcriptional regulations of anthocyabetween vegetative and reproductive organs in Brassica crops. At the same time, DFR(AT5G42800), MYB5(AT3G13540) and AHA10(AT1G17260) were differentially expressed in eight developmental stages of five Brassica crops, especially DFR(AT5G42800), which iwa generally considered to be the target gene of the MBW transcriptional regulatory complex, was not differentially expressed only in B. juncea (Fig.…”
Section: Co-expression Analysis Of Anthocyanin-related Genescontrasting
confidence: 99%
See 1 more Smart Citation
“…4, Supplementary Table S2). This was different from the results we discovered that only PAP1/2 homologous copies were differentially expressed in green and purple leaves of five Brassica crops [5], indicating the different transcriptional regulations of anthocyabetween vegetative and reproductive organs in Brassica crops. At the same time, DFR(AT5G42800), MYB5(AT3G13540) and AHA10(AT1G17260) were differentially expressed in eight developmental stages of five Brassica crops, especially DFR(AT5G42800), which iwa generally considered to be the target gene of the MBW transcriptional regulatory complex, was not differentially expressed only in B. juncea (Fig.…”
Section: Co-expression Analysis Of Anthocyanin-related Genescontrasting
confidence: 99%
“…The read counts of each gene were calculated using the htseq-count function in htseq software [1]. The R package DEseq2 (v1.16.1) was used to identify the differentially expressed genes (DEGs) between leaves of different colors based on the following criteria: padj < 0.05 & log2FoldChange > 2 [5].…”
Section: Expression Profiles Analysis Based On Rna-seq Datamentioning
confidence: 99%
“…The evolution of the R2R3-MYB gene family in Brassica has been tracked in previous research [ 21 ]. In order to specifically understand the evolutionary relationship of target genes, we analyzed the homologous relationship among Arabidopsis , B. napus (A and C subgenomes), B. rapa (A genome), and B. oleracea (C genome) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study [ 21 ], 2120 R2R3-MYB genes were identified in six brassica plants, including 130 in Arabidopsis , 236 in B. rapa , 247 in B. oleracea , 248 in B. nigra , 425 in B. napus , 422 in B. juncea and 412 in B. carinata . However, the number of R2R3-MYBs in Arabidopsis , B. rapa and B. napus were different from those found in previous studies, namely, 126 in Arabidopsis [ 18 ], 256 in B. rapa [ 22 ], and 249 in B. napus [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The read counts of each gene were calculated using the htseq-count function in htseq software (Anders et al, 2015). The R package DEseq2 (v1.16.1) was used to identify the differentially expressed genes (DEGs) between leaves of different colors based on the following criteria: padj < 0.05 & log2FoldChange > 2 (Chen et al, 2022).…”
Section: Expression Pro Les Analysis Based On Rna-seq Datamentioning
confidence: 99%